MANAJEMEN PEMBELAJARAN MATEMATIKA MENGGUNAKAN MEDIA BENDA KONKRIT - Surani Surani (Manajer Pendididikan, 2017)
The purpose of the study is to determine the learning outcomes after the implementation of mathematics learning management using concrete object media. This type of research is a classroom action research. The data were collected by evacuation test, documentation, and observation. The sample of the research is the populative sample that is all the population member used as the research sample. Results of mathematics learning showed that students have better mastery of material compared with the learning process that does not use concrete objects media with the assumption that the weight of the material is balanced.